La documentación histórica de la Universidad de Cervera: La figura del cancelario Dr. Francisco J. F - Prat Sedeño, Judith (Revista General de Información y Documentación, 2004)
The documentary analysis of the academic and human trajectory of Francisco J.Fuertes Piquer (17171789) acquires a representative value of great importance in understanding the enlightened reforms affecting the Spanish university in the XVIII century. This century is defined by the local peculiarities of the lesser universities together with the progressive move towards uniformity of all the universities of the Monarchy, and the perennial tension between the gremial character of the university institution and the possible influence of the powers public is likewise noteworthy. The present article is an in-depth study of Fuertes Piquer prior to his becoming chancellor of the University of Cervera (Jewel Deposit taker and Deputy in the Monte de Piedad at Madrid and, at the same time, schoolboy, professor, and Director of the University of Alcalá) and how these experiences influenced his work as the chief authority of the University of Cervera from 1762 to 1789, the year of his death.